Ascites-Derived Extracellular microRNAs as Potential Biomarkers for Ovarian Cancer - Záveský, Luděk; Jandáková, Eva; Weinberger, Vít; Minář, Luboš; Hanzíková, Veronika; Dušková, Daniela; Drábková, Lenka Záveská; Svobodová, Iveta; Hořínek, Aleš (Reproductive sciences, 2019)
Ovarian cancer as the most fatal gynecological malignancy is often manifested by excessive fluid accumulation known as ascites or effusion. Ascites-derived microRNAs (miRNAs) may be closely associated with ovarian cancer progression. However, our knowledge of their roles, altered expression, and clinical outcomes remained limited. In this study, large-scale expression profiling of 754 human miRNAs was performed using real-time quantitative polymerase chain reaction and 384-well TaqMan array human miRNA A and B cards to identify differentially expressed miRNAs between extracellular fraction of the ascitic fluid associated with high-grade serous ovarian carcinomas and control plasma. Of the 754 miRNAs, 153 were significantly differentially expressed relative to the controls. Expression of 7 individual miRNAs (miR-200a, miR-200b, miR-200c, miR-141, miR-429, miR-1290, and miR-30a-5p) was further validated in extended sample sets, including serous, endometrioid, and mucinous subtypes. All miR-200 family members and miR-1290 were conspicuously overexpressed, while miR-30a-5p was only weakly overexpressed. The ability of miRNAs expression to discriminate the pathological samples from the controls was strong. Receiver operating characteristic curve analyses found area under the curve (AUC) values of 1.000 for miR-200a, miR-200c, miR-141, miR-429, and miR-1290 and of AUC 0.996 and 0.885 for miR-200b and miR-30a-5p, respectively. Preliminary survival analyses indicated low expression level of miR-200b as significantly related to longer overall survival (hazard ratio [HR]: 0.25, mean survival 44 months), while high expression level was related to poor overall survival (HR: 4.04, mean survival 24 months). Our findings suggested that ascites-derived miRNAs should be further explored and evaluated as potential diagnostic and prognostic biomarkers for ovarian cancer.
Keywords: extracelulární tekutina; MicroRNAs; Ovarian Neoplasms; Kaplan-Meier Estimate; mikro RNA; Adult; Kaplanův-Meierův odhad; Aged; dospělí; senioři; lidé středního věku; nádory vaječníků; ascites; senioři nad 80 let; Extracellular Fluid; lidé; ženské pohlaví; Humans; Aged, 80 and over; Ascites; Female; Biomarkers, Tumor; nádorové biomarkery; Middle Aged